2008
DOI: 10.1055/s-2008-1061622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Semantic Impairment on Language Use in Alzheimer's Disease

Abstract: Many studies present apparently conflicting results and conclusions about the effects of Alzheimer's disease (AD) on language use. This review attempts to reconcile these apparently conflicting results regarding the language impairments in AD by discussing how the slow deterioration of the semantic system at the feature level interacts with the task demands of tests used to evaluate performance. In particular, performance is impaired on tasks that require relatively complete, elaborate semantic representations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 99 publications
0
22
0
4
Order By: Relevance
“…In addition, several studies of word priming (Glosser et al, 1998; Milberg et al, 1999; Salmon et al, 1988) have reported significant deficits in Alzheimer dementia patients, although other studies have failed to find this effect (Nebes & Brady, 1988). For a recent review of this area, see Altmann & McClung (2008).…”
Section: Patients With Ad Dementiamentioning
confidence: 99%
“…In addition, several studies of word priming (Glosser et al, 1998; Milberg et al, 1999; Salmon et al, 1988) have reported significant deficits in Alzheimer dementia patients, although other studies have failed to find this effect (Nebes & Brady, 1988). For a recent review of this area, see Altmann & McClung (2008).…”
Section: Patients With Ad Dementiamentioning
confidence: 99%
“…In addition to loss of memory, AD is known for a decline in productive language (Blair, Marczinski, Davis-Faroque & Kertesz, 2007; Kemper, Greiner, Marquis, Prenovost & Mitzner, 2001; Kempler, 1995). Various components of language have been examined in order to specify the nature of the expressive language decline, with the literature predominantly showing a decline in semantically intact communication reflected in reduced productive vocabulary (Altmann & McClung, 2008). In contrast, syntax has been identified as an aspect of language that is relatively preserved in AD (Kempler & Zelinski, 1994), although some controversy in this area remains (Bates, Harris, Marchman & Wulfeck, 1995).…”
mentioning
confidence: 99%
“…A second hypothesis, which is more frequently discussed in the literature, proposes impairment of the semantic system. Indeed, many authors propose the hypothesis of a progressive deterioration of the semantic representations stored in long-term memory [7,8,9,10,11]. Others, such as Rogers and Friedman [12], evoke the possibility of incomplete access to the semantic system.…”
Section: Introductionmentioning
confidence: 99%